LEGAL PROTECTION FOR USERS OF INTERNET BANKING CUSTOMERS FOLLOWING CHANGES IN INFORMATION AND ELECTRONIC TRANSACTIONS LAW - Azharuddin Azharuddin (Jurnal Pembaharuan Hukum, 2019)
The presence of the Internet Banking service has offered a number of convenience and flexibility in conducting transactions, both between the bank and its customers, the bank and merchant, bank with the bank and the customer with the customer. However, this simplicity does not mean no risk. In addition to the Internet Banking service provides convenience, also in fact have some risks. The risk of a new character and is a challenge for practitioners and experts in the field of Internet Banking service to handle it, so it becomes important to discuss the legal efforts to protect customers' personal data in the operation of Internet Banking service after changes in legislation and elektronic information transaction. Forms of protection against customer data in Internet Banking in Indonesia are from several types of regulations that have regulated internet banking, namely Bank Indonesia Regulation Number 9/15 / PBI / 2007 concerning Application of Risk Management in the Use of Information Technology by Commercial Banks and Act No. 19 of 2016 concerning Amendments to Act No. 8 of 2011 concerning Electronic Information and Transactions along with the Financial Services Authority Act in the section on consumer protection